Avaliação de indutores de resistência biótico, abiótico e extratos vegetais no controle de Meloidogyne incognita em tomateiro - Formentini, Heloísa Maria (2012)
In Brazil, the tomato is one of the vegetable species of great importance both economically and socially, however several factors are limiting its production as an example the diseases caused by nematodes of the genus Meloidogyne that limit the production in infested areas. Seeking new measures of protection and control of plant disease induced resistance is na alternative considerering that little attention has been directed to the possibility of induced resistance to root pathogens like nematodes. Therefore, this study aimed to verify the effectiveness of the chemical inducer acibenzolar-S-methyl, the biotic inductor Bacillus cereus and plant extracts of rosemary (Rosmarinus officinalis) and turmeric (Curcuma longa) in the induced resistance in susceptible and resistant tomato in plants infected with Meloidogyne incognita race 3. Two experiments were conducted simultaneously both followed the 2 x 6 factorial design with two tomato genotypes, one susceptible to M. incognita (Santa Clara) and a resistant (Ivety) and six treatments: ASM (125 mg i.a L -1 ), Bacillus cereus (6.10 7 CFU mL -1 ), rosemary 10%, turmeric 10%, water and a control (no inoculum and no spraying in the aerial part), with five replicates. Each vase with a capacity of 2 L, were filled with a mixture of soil, sand and compost previously autoclaved and homogenized in the ratio 2:2:1 and were transplanted to each one three tomato seedlings susceptible and resistant. The treatments were sprayed in the aerial part in tomato plants in all vases except the absolute control. At 72 h after the first application of treatments was carried out the inoculation of 407/100 cm 3 of J2 and eggs per vase. In the first experiment, using destructive samples of tomato treated and inoculated with M. incognita were determined the response of both genotypes to the treatments applied to the enzymatic activity of peroxidase, polyphenol oxidase, chitinase, β-1,3 glucanase and phenylalanine ammonia-lyase from roots of tomato plants that were macerated and homogenized to withdrawals in time 0 h, 24 h, 48 h, 96 h and 120 h after the first application of the treatments. In the second experiment, the variables analyzed to determine the effect of treatments on nematode population were the number of root-knots, juveniles and eggs in the soil accomplished at 56 days after the first application of the treatments that were reapplied every seven days during this period. From the results obtained it was concluded that there was a reduction in the number of root-knots in the roots of tomato plants showing no difference between the two genotypes for plants that received the treatments with acibenzolar-S-methyl, turmeric, rosemary and B. cereus. There was a reduction in the formation of root-knots in susceptible cultivar, confirming their potential in protecting the genotypes used against the attack of M. incognita. For the enzimatic activity peroxidase was the enzyme strongly associated with resistance with the highest activity in resistant genotype if compared to susceptible regardless of inducer treatment. In susceptible tomato B. cereus stood out in the induction of chitinase and peroxidase whereas for the resistant tomato rosemary induced peroxidase and polyphenol oxidase and rosemary extracts and turmeric induced chitinase enzyme to the susceptible genotype